A Client-Side Architecture for Enhancing Productivity of Interactive Parallel Scalability Analysis with PaScal Suite - Correia, Igor Sérgio de França; Xavier-de-Souza, Samuel (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2025: Anais do XXVI Simpósio em Sistemas Computacionais de Alto Desempenho, 2025)
Traditional profilers struggle with scalability analysis. The PaScal Suite’s Viewer tool addresses this, but its server-side architecture creates performance bottlenecks with large datasets. This paper proposes a client-side Single-Page Application (SPA) architecture that transfers all data processing to the browser, enabling fluid, instantaneous analysis. We also introduce a novel hierarchical visualization for comparing code regions, which simplifies diagnostics. The result is an agile platform that enhances the identification of scalability bottlenecks.